γ-Secretase-Regulated Signaling Typified by Notch Signaling in the Immune System - Nagase, Hisashi; Nakayama, Kohzo (Current Stem Cell Research & Therapy, 2013)
Notch signaling mediates the fates of numerous cells not only in the nervous system but also in the immune system. Notch signaling contributes to the generation and maintenance of hematopoietic stem cells, lymphocyte development, and several immune responses. The molecular mechanism of Notch signaling is unique: ligands bind to the extracellular domain of Notch and trigger sequential proteolytic cleavages. Finally, γ-secretase releases the intracellular domain (ICD) of Notch (NICD) from the cell membrane, and NICD translocates to the nucleus. In the nucleus, NICD binds to transcription factors and modifies the expression of certain genes. Thus,γ-secretase controls Notch signaling. Recently, many type 1 transmembrane proteins have been reported to be substrates for γ-secretase, and their ICDs are released from the cell membrane to the cytoplasm. It has also been reported that ICDs of several of these substrates also translocate to the nucleus. These phenomena closely resemble that of Notch signaling. Therefore, the common enzyme γ-secretase controls the proteolysis and turnover of possible signaling molecules, which has led to the hypothesis that mechanisms similar to Notch signaling contribute widely to γ-secretase-regulated signaling pathways. Indeed, we have shown that the ICD of amyloid precursor protein (APP) alters gene expression and induces neuron-specific apoptosis. These observations suggest the existence of APP signaling that is controlled by γ-secretase. It is also likely that γ-secretase-regulated signaling pathways, besides Notch signaling, play an essential role in the immune system. In fact, CD44, which is involved in hematopoiesis and lymphocyte homing, seems to have a γ-secretase-regulated signaling mechanism. In this review, we focus not only on Notch signaling but also on other γ-secretase-regulated signaling pathways in the immune system.
Keywords: Intracellular domain (ICD)